Negative Regulation of Interferon-β Production by Alternative Splicing of Tumor Necrosis Factor Receptor-Associated Factor 3 in Ducks - Wei, Xiaoqin; Qian, Wei; Sizhu, Suolang; Li, Yongtao; Guo, Kelei; Jin, Meilin; Zhou, Hongbo (Frontiers in Immunology, 2018)
Tumor necrosis factor receptor-associated factor 3 (TRAF3), an intracellular signal transducer, is identified as an important component of Toll-like receptors (TLRs) and RIG-I-like receptors (RLRs) induced type I interferon (IFN) signaling pathways. Previous studies have clarified TRAF3 function in mammals, but little is known about the role of TRAF3 in ducks. Here, we cloned and characterized the full-length duck TRAF3 (duTRAF3) gene and an alternatively spliced isoform of duTRAF3 (duTRAF3-S) lacking the fragment encoding amino acids 217 to 319, from duck embryo fibroblasts (DEFs). We found that duTRAF3 and duTRAF3-S played different roles in regulating IFN-β production in DEFs. duTRAF3 through its TRAF domain interacted with duMAVS or duTRIF, leading to the production of IFN-β. However, duTRAF3-S, containing the TRAF domain, was unable to bind duMAVS or duTRIF due to the intramolecular binding between the N- and C-terminal of duTRAF3-S that blocked the function of its TRAF domain. Further analysis identified that duTRAF3-S competed with duTRAF3 itself for binding to duTRAF3, perturbing duTRAF3 self-association, that impaired the assembly of duTRAF3-duMAVS/duTRIF complex, ultimately resulted in a reduced production of IFN-β. These ﬁndings suggest that duTRAF3 is an important regulator of duck innate immune signaling and reveal a novel mechanism for the negative regulation of IFN-β production via changing the formation of the homo-oligomerization of wild molecules, implying a novel regulatory role of truncated proteins.